The association of human leukocyte antigen polymorphisms with disease severity and latency period in patients with silicosis - Dogan, Hasan (BioMed Central, 2014)
BACKGROUND: Denim sandblasting may cause silicosis as a result of free crystalline silica inhalation. Its pathogenesis remains unclear, but autoimmunity may play a role in the development of silicosis. The present study aimed to investigate the relationships between human leukocyte antigen (HLA) and the severity and latency period of silicosis. METHODS: 48 silicotic patients in the Eastern part of Turkey were classified according to their latency period and disease severity. The distribution of HLAs according to disease severity and latency period was assessed. RESULTS: A23 (7.5%), B49 (7.5%), and B51 (25%) were more common in the mild group than in the severe group, and B55 (8.9%) and DR4 (17.9%) were more common in the severe group than in the mild one. Only B51 was significantly more common in the mild group than in the severe one (25%, n = 10 vs. 7.1%, n = 4; p = 0.016). CONCLUSIONS: This study suggests that HLA antigens may play a particular role in the severity of silica-induced lung disease, but there was no association between HLA and progression time of the disease.